685 Understanding mental health symptoms suffered by traumatic brain injury patients in Moshi, Tanzania. (1st September 2016) - Vissoci, João Ricardo Nickenig; Kwesigabo, Joan; Geffrey, Green; Mvungi, Mark; Staton, Catherine
Abstract : Background: Traumatic Brain Injury (TBI) is the most common cause of injury death and disability globally. While TBI increases mental health burden, there is no current literature in low and middle-income countries (LMIC) about these patients. This project evaluated the pre-injury mental health of TBI at the Kilimanjaro Christian Medical Centre (KCMC) in Moshi, Tanzania. Methods: Surveys were conducted of TBI patients between May September 2015. Participants were >18 years old and responded at discharge the questionnaires: PHQ-9, Kessler, CES-D, and AUDIT. Data were descriptively represented and questionnaires classified according to the cut-offs: PHQ-9 >4, CES >15, Kessler >20, and AUDIT >7. Frequences, means with standard deviations (sd) were reported and a spearman correlation was used to evaluate associations. Results: Of all 77 TBI patients, most are male (84%) with mean age of 35 (sd 13) and married (61%). Patients were mainly farmers, skilled or unskilled workers or work in business. While a small percentage of patients have signs of depression (2.6% to 9.1%) and anxiety (4.2%) prior to their injury, a significant proportion have harmful or hazardous drinking behaviour (42.9%). A moderate correlation was observed between depression and anxiety symptoms (R = 0.44 and R = 0.51). A small and not significant association was found between hazardous or harmful drinking and depression (R = −0.02 and R = −0.09) or anxiety (R = 0.02) amongst this population. Conclusions: This is the first report of pre-injury mental health of TBI patients in Tanzania. Although significant proportions of patients did not show large mental health systems hazard or harmful alcohol use was concerningly high. However, association patterns demonstrated that patients with harmful or hazardous drinking are not the same with depression and anxiety score. This is an important preliminary finding to understand the baseline mental health status of our TBI patients in a low income setting.